The future of philosophy of mind - Braun, Ricardo (2007)
In this essay the main topics in contemporary philosophy of mind are presented and discussed. They show the current mainstream in the philosophy of mind and the projection for the years to come. In addition, the function of philosophy of mind in the advancement in the understanding of mental phenomena is highlighted. The following topics are addressed: The importance of philosophy in psychology; contemporary dualism and its repercussions on the physicalist conception of the mental is addressed; reductionism and eliminativism are discussed; individualism and the constriction on the science of psychology; and lastly, the relationship between brain and consciousness.